Methods for the 2019 New Zealand family violence study- a study on the association between violence exposure, health and well-being. (2nd January 2021) - Fanslow, Janet; Gulliver, Pauline; Hashemi, Ladan; Malihi, Zarintaj; McIntosh, Tracey
ABSTRACT: Family violence, which includes child abuse, intimate partner violence and elder abuse, is a problem of national and global significance. Robust evidence about the scale and consequences of the problem is needed to inform policy and practice, including information on high-risk groups, and risk and protective factors. In this article, the methods utilised for collecting data for NZ's 2019 Family Violence Survey are described, along with a summary of the characteristics of the population-based sample obtained. The 2019 NZ Family Violence Survey will provide prevalence estimates of violence exposure for women and men across a wide range of types of violence across the lifespan. This article provides a basis for understanding who was included in the study sample, and for enabling understanding and interpretation of future study findings.